2023
DOI: 10.3390/molecules28020737
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Solid Dispersion of Polygonum Cuspidatum Extract by Hot Melt Extrusion to Enhance Oral Bioavailability of Resveratrol

Abstract: The aim of this study was to improve the solubility, bioavailability, and stability of resveratrol (RES-SD) Solid Dispersion in Polygonum cuspidatum extract (PCE) by hot melt extrusion (HME). In addition, the role of the auxiliary substances in PCE was also studied. The solid dispersion of Polygonum cuspidatum extract was prepared by hot-melt extrusion. The optimum formula was selected by single factor design and orthogonal test. The optimum formula was barrel temperature 140 °C, screw rotation speed 40 rpm/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…A previous study regarding HME-orientated antihypertensive molecules revealed high levels of bioavailability in a rat model [28]. Another study on HME-orientated resveratrol confirmed an improvement in the solubility and oral bioavailability of resveratrol [29]. A previous animal study also confirmed improvements in the oral bioavailability and biological effects of cyclosporine through HME [30].…”
Section: Discussionmentioning
confidence: 66%
“…A previous study regarding HME-orientated antihypertensive molecules revealed high levels of bioavailability in a rat model [28]. Another study on HME-orientated resveratrol confirmed an improvement in the solubility and oral bioavailability of resveratrol [29]. A previous animal study also confirmed improvements in the oral bioavailability and biological effects of cyclosporine through HME [30].…”
Section: Discussionmentioning
confidence: 66%
“… PCE-SD improved RES's oral bioavailability and solubility. [ 246 ] AUC0-t: the extrapolated area under the concentration-time curve; CPP: cell-penetrating peptide; EtOH: ethanol; HUVECs: human umbilical vein endothelial cells; H 2 O: water; IC50: half-maximal inhibitory concentration; MeOH: methanol; RES: resveratrol; SD: solid dispersion. …”
Section: Phytopharmaceutical Formulationsmentioning
confidence: 99%